Intestinal microbial profiling and immune responses of hybrid snakehead (Channa maculata ♀ × Channa argus ♂) challenged with Nocardia seriolae strain - Zhou, Tingting; Cai, Ping; Li, Junwei; Li, Zhongsheng; Dan, Xueming (Aquaculture reports, 2024)
Nocardiosis in fish, caused by Nocardia seriolae (a kind of filamentous bacterium), is a severe disease in aquaculture, affecting over 40 species of marine and freshwater fish and causing great losses. To investigate the relationship between fish nocardiosis and the gut microbiota, we first artificially infected hybrid snakehead (female Channa maculata × male Channa argus) with N. seriolae (1.0 × 107 CFU/mL), then utilized techniques such as high-throughput sequencing of 16 S rRNA, histopathology, and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) to analyze the changes in microbial community structure, intestinal histopathological characteristics, and related immune genes expression in hybrid snakehead. Changes in gut microbial community structure and diversity were observed starting from day 2, followed by fluctuations on day 4, and significant alterations on day 6. Four major phyla (Actinomycetes, Proteobacteria, Firmicutes, and Bacteroidetes), particularly Actinomycetes, reflected the temporal variations in the gut microbiota structure. The composition of the gut microbiota also underwent significant changes, with beneficial microorganisms such as Lactobacillus decreasing and harmful microorganisms such as Aeromonas and Nocardia increasing. The pathological sections showed that after N. seriolae injection, the fish intestinal villi became distorted and widely spaced, with increasing damage over time, leading to severe shrinkage and atrophy by the sixth day. Additionally, immune-related genes, such as TLR2 and IRF2, exhibited higher mRNA expression levels (P < 0.01) in the intestinal tissues of the infected fish. Overall, this study provides preliminary insights into the dynamic changes in gut microbial community, immune response, and intestinal pathogenic mechanisms during N. seriolae infection in hybrid snakehead, at both the levels of gut microbial composition and mRNA expression. These findings are important for better understanding and managing Nocardia infection in fish. •Nocardia seriolae significantly damaged hybrid snakehead intestinal tissues.•N. seriolae greatly altered the diversity and composition of the gut microbiota in snakehead.•The immune-related genes like TLR2 and IRF2 were highly expressed in intestinal tissues.